Per un'altra Firenze Voci sul futuro del nostro patrimonio - Migaleddu, Sara; Lovino, Orazio; PESCARMONA, GIOVANNI (Dialoghi con la società, 2020)
The Covid-19 pandemic has had unprecedented and dramatic consequences on the cultural activities and the development of tourism in italian cities. In the midst of this scenario, the Department of History, Archeology, Geography, Art, and the Performing Arts (SAGAS) of the University of Florence organized three days of online conferences in which representatives of political and cultural institutions, along with qualified observers, expressed their views on the future of cultural policy after the health crisis. This book is a collection of all those "voices on the future of our heritage" that spoke in this series of videoconferences. This publication aims at ensuring that they can be heard by a wider audience, to start a reflection on the possibility of redesigning Florence's cultural and touristic offerings. To bring about such a change, it is necessary to think within a new framework, one that aims at integrating itineraries capable of embracing the entire city, its histories, and its communities.